JUSTIFICATION OF ESTABLISHING BUILDING PERMITS FOR PRIVATE EDUCATION INSTITUTIONS WAQF BASED ON THE PERSPEKTIF GOVERNMENT SOCIAL RESPONSIBILITY - Muhammad Aminulloh; Endeh Suhartini (Magister Hukum Sekolah Pascasarjana Unida, 2017)
Indonesia as a developing country is still trying to do development, this development requires the Legal Certainty for the realization of efforts community life. [Article 1 paragraph (3) of the 1945 Constitution (after amendment). In fact, legislation relating to development still overlaps policies, resulting in the existence of Legal Uncertainty. Example; Perda IMB pertains to the services of authorized officers. Governments use planning to manage land development of their jurisdictions. Thus, government units can plan community needs while safeguarding natural resources. A building permit is required in accordance with the spatial, land use planning (land use plan). The government makes rules on the land guidance plan, one of which is the rule of article 2, paragraph 1 of the BAL, the state regulates the use, allocation, provision and maintenance, usage, designation (utilization, KDB, outbreaks, apartment buildings, irrigation buildings, etc.). How to use the land, there are rules, the rules can be location permit, IPPT, land use permit, building permit, why should use IMB, as this is to regulate in the framework of the maintenance of the livelihood of the people and this applies to all, and schools, social schools, including educational institutions that stand on wakaf land managed by the foundation. For educational institutions, it is felt to be heavy in terms of obtaining building permits. this is because the process of permission to build the building was equated with the lisence establishment of factories, industries etc. Besides that, the heavy rules so far felt by institutions that will establish school schools to licensing issues are the rules on AMDAL. The government is afraid of land use will be wrong. AMDAL is requirements for the establish of a school. The government should make a classification rule on AMDAL for building permits for the establishment of schools, especially school schools located in waqf land, lighter than building permits for industrial or factory establishments. (descriptions of AMDAL). The importance of building lisence (IMB) can be a starting point in obtaining legal certainty to the right of building so that disturbance or harmful things, and to gain comfort in using the buildingKeywords: IMB, Land of Waqf and Government Social Responsibility